Screening Green Manure Cover Crops for their Allelopathic Effects on Some Important Weeds Found in Zimbabwe - M, Runzika; J. T, Rugare; S, Mabasa (Asian Journal of Agriculture and Rural Development, 2013)
Weed control is a serious problem in smallholder conservation agriculture farming areas in Zimbabwe. Green Manure Cover Crops (GMCCs), which improve soil fertility and reduce weeds through allelopathy, are likely to reduce the cost of weed control in these areas. A laboratory study was conducted at the University of Zimbabwe to investigate the effect of extracts of eleven GMCCs on the germination percentage, radicle and plumule length of Bidens pilosa, Eleusine indica and Pennisatum glaucum (pearl millet). A green house experiment was also done to determine the allelopathic potential of these GMCC extracts applied as soil incorporated residues on the emergence and dry matter production of E. indica, B. pilosa and Acanthospermum hispidum. GMCC extracts significantly reduced germination, radicle and plumule length of Pennisatum glaucum (P < 0.05) except for Crotalaria grahamiana and Raphanus sativas which had no effect on germination of Pearl millet. The emergence and dry matter of B. pilosa, E. indica and A. hispidum were significantly reduced by these legumes (P < 0.05) with the exception of common vetch (Vicia sativa) which stimulated the emergence of A. hispidum. Most of the legumes that were used in this study have allelopathic effects on B. pilosa, E. indica and A. hispidum.